Analisa Perbandingan Sikap Rasional Produsen Konvensional dengan Tujuan Memaksimalkan Keuntungan dan Sikap Rasional-Islami Produsen Muslim dengan Tujuan Memaksimalkan Maslahah - Dwi Umardani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This research is conducted to find out the attitude differences of conventional producer and moslem producer on various economic cases. The method used is a qualitative method with primary and secondary data collected through literature review and analyzed using a comparative method. The results found that since the source of knowledge of the two producers are different, both have many different attitudes on various economic cases; such as (1) According to conventional producer, the true meaning of profit is profit in the material sense, while according to moslem producer, the true meaning of profit is profit in the material and immaterial sense (2) Conventional producer will tend to follow all market demands, while moslem producer will only follow market demands that are in line with the values ​​of wahyu (3) In the perspective of conventional producer, the principle of implementing CSR activities is because it is required by laws and regulations as well as rational awareness to create a conducive corporate environment to maximize material profit, , while from the perspective of moslem producer, the principle of implementing CSR activities is not only because it is required by laws and regulations but more than that because those social responsibility activities are ordered by Allah SWT as well as the rational-islamic awareness that creating a conducive corporate environment can maximize two profits at once, namely material and immaterial profits (4) Conventional producer will create products that can increase consumer utility, while moslem producer will create products that can maximize consumer maslahah.